An immunostaining-based approach for assessing myocardial viability in the infarcted mouse hearts - Ouyang, Weili; Liu, Xueqing; Ding, Zheheng; Ji, Yanan; Zhao, Jianfeng; Zhu, Hongtao; Wu, Weidong; Ding, Zhaoping (Frontiers in Cardiovascular Medicine, 2025)
IntroductionWith the growing need for reliable and precise detection of cell viability in spatial biology, we introduce an antibody-based staining of cardiac troponin I (cTnI) as a simple yet valuable tool for delineating cardiomyocyte viability in the early stages of myocardial infarction (MI).Methods & ResultsIn circulation, cTnI was found to be the most abundantly released biomarker within the first 24 h after MI. In heart sections, partial depletion of cTnI staining was observed within dying cardiomyocytes as early as 6 h, with almost absence by 24 h despite of preserved membrane integrity. In contrast, staining for other sarcomeric proteins, such as troponin T and α-actinin, remained detectable for several days until immune cells infiltration occurred. We further validated the rapid loss of cTnI staining by cross-verifying in-vivo and ex-vivo measurements. Notably, cTnI-stained sections showed precise overlap with TTC-stained images at the cellular level and showed a highly consistent pattern of cardiomyocyte distribution and infarct area (r² = 0.96) when compared to in-vivo measurements using manganese-enhanced magnetic resonance imaging (MEMRI).ConclusionThese findings highlight the coordinated, stepwise breakdown of sarcomeric proteins following ischemic injury in the mouse heart and underscore the utility of antibody-based cTnI staining as a valuable tool for early myocardial viability assessment and infarct area detection with high spatial resolution.